2019
DOI: 10.1007/s00428-019-02577-x
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning for automatic Gleason pattern classification for grade group determination of prostate biopsies

Abstract: Histopathologic grading of prostate cancer using Gleason patterns (GPs) is subject to a large inter-observer variability, which may result in suboptimal treatment of patients. With the introduction of digitization and whole-slide images of prostate biopsies, computer-aided grading becomes feasible. Computer-aided grading has the potential to improve histopathological grading and treatment selection for prostate cancer. Automated detection of GPs and determination of the grade groups (GG) using a convolutional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
94
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(94 citation statements)
references
References 26 publications
0
94
0
Order By: Relevance
“…The resulting moderate level of inter-rater agreement that we found for both HE and FCM is consistent with other findings, as far as grading is concerned. Actually, an interobserver variability in Gleason attribution has already been documented for HE analyses [4,6,18]. In the Ozkan et al's study [19], the interobserver concordance was reported to be 58% (K = 0.43) with respect to the Gleason sum.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The resulting moderate level of inter-rater agreement that we found for both HE and FCM is consistent with other findings, as far as grading is concerned. Actually, an interobserver variability in Gleason attribution has already been documented for HE analyses [4,6,18]. In the Ozkan et al's study [19], the interobserver concordance was reported to be 58% (K = 0.43) with respect to the Gleason sum.…”
Section: Discussionmentioning
confidence: 88%
“…The ISUP 2014 update aimed to improve the reproducibility of grading; however, a certain degree of interobserver variability still persists and is similar to the one described for conventional Gleason scoring [18]. This is the basis for most of the second opinion requirement, which can lead to a degree of discrepancy close to 45% (K = 0.46) [20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Working speed of the machine allowed the analysis of hundreds of slides in a few hours. With different AI models, [45][46][47] found identical results with a good concordance between pathologist and a CNN model, with high accuracy, sensibility, and specificity in diagnosing and differentiating low and high-grade PCa. Arvaniti et al [48] provided additional information.…”
Section: Pathologymentioning
confidence: 79%
“…One option could be image recognition by finding comparable visual characteristics by texture analysis . Another possibility is to use tissue recognition using similar deep learning algorithms now used in histology . OCT images with a higher resolution could improve these two options, allowing more subtle differences to be detected.…”
Section: Discussionmentioning
confidence: 99%